Agrimonia procera Wallr. Extract Increases Stress Resistance and Prolongs Life Span in Caenorhabditis elegans via Transcription Factor DAF-16 (FoxO Orthologue) - Christina Saier; Inge Gommlich; Volker Hiemann; Sabrina Baier; Karoline Koch; Gert Horn; Tanja Kowalewsky; Jörg Bartelt; Maria Seemann; Wim Wätjen (MDPI AG, 2018)
Agrimonia procera is a pharmacologically interesting plant which is proposed to protect against various diseases due to its high amount of phytochemicals, e.g., polyphenols. However, in spite of the amount of postulated health benefits, studies concerning the mechanistic effects of Agrimonia procera are limited. Using the nematode Caenorhabditis elegans, we were able to show that an ethanol extract of Agrimonia procera herba (eAE) mediates strong antioxidative effects in the nematode: Beside a strong radical-scavenging activity, eAE reduces accumulation of reactive oxygen species (ROS) accumulation and protects against paraquat-induced oxidative stress. The extract does not protect against amyloid-β-mediated toxicity, but efficiently increases the life span (up to 12.7%), as well as the resistance to thermal stress (prolongation of survival up to 22%), of this model organism. Using nematodes deficient in the forkhead box O (FoxO)-orthologue DAF-16, we were able to demonstrate that beneficial effects of eAE on stress resistance and life span were mediated via this transcription factor. We showed antioxidative, stress-reducing, and life-prolonging effects of eAE in vivo and were able to demonstrate a molecular mechanism of this extract. These results may be important for identifying further molecular targets of eAE in humans.